The Moderating Effect of Job-Embeddedness on the Relationships between Organizational Socialization and Job Performance and between Organizational Socialization and Employee Well-Being - Chotigavanich, Charatpong; Sorod, Bung-on (Journal of Community Development Research (Humanities and Social Sciences), 2020)
Organizational socialization and job-embeddedness are among the tools and interventions that have long been used by practitioners to help newcomers better adjust to corporate culture and to increase employees’ retention. This study examines the relationships between organizational socialization and the employee’s performance and between organizational socialization and the well-being of salespersons Thailand. Specifically, it aims to explore the moderating effect of job-embeddedness on those relationships. Understanding the relationships and the moderating effect of the variables as mentioned above can provide corporates with deeper insights into how to enhance employees’ productivity and capability. Data were collected from 422 salespersons of consumer products, cosmetics, consumer real estate, and whole sale pharmaceutical companies in Thailand. The data analyses showed statistically significant and positive relationships between organizational socialization and employee’s performance and between organizational socialization and the employee’s well-being. The analysis also indicated the moderating effect of job-embeddedness on the relationship between organizational socialization and the employee’s performance, but not on the relationship between organizational socialization and well-being. Implications and suggestions for future research are discussed. Keywords: Job Embeddedness, Organizational Socialization, Role-Based Performance, Well-Being, Thai Sales Personnel